1999
DOI: 10.1016/s0304-3959(98)00258-9
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of pain perception across the menstrual cycle

Abstract: The purpose of this article is to review the sixteen published studies that examine associations between the perception of experimentally induced pain across menstrual cycle phases of healthy females. We also performed a meta-analysis to quantitatively analyze the data and attempt to draw conclusions. The results suggest that there are relatively consistent patterns in the sensitivity to painful stimulation. These patterns are similar across stimulus modality with the exception of electrical stimulation. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
292
5
15

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(326 citation statements)
references
References 45 publications
14
292
5
15
Order By: Relevance
“…Thus far, it has been determined that caveolin proteins functionally link estrogen receptors with mGluRs in striatal neurons [92]; other regions await verification. Through influencing these additional regions, rapid estrogen receptor signaling has been suggested to modulate multiple cellular processes, such as motor control and drug addiction [12,[95][96][97], sexual receptivity [91], the control of the estrous cycle [98], and nociception [14,99]. Furthermore, while we and others hypothesize GPCRs to act as intermediaries between estrogen receptors and G proteins, others have postulated that estrogen receptors directly activate the G proteins [100].…”
Section: Caveolin Proteins and Estrogen Receptorsmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus far, it has been determined that caveolin proteins functionally link estrogen receptors with mGluRs in striatal neurons [92]; other regions await verification. Through influencing these additional regions, rapid estrogen receptor signaling has been suggested to modulate multiple cellular processes, such as motor control and drug addiction [12,[95][96][97], sexual receptivity [91], the control of the estrous cycle [98], and nociception [14,99]. Furthermore, while we and others hypothesize GPCRs to act as intermediaries between estrogen receptors and G proteins, others have postulated that estrogen receptors directly activate the G proteins [100].…”
Section: Caveolin Proteins and Estrogen Receptorsmentioning
confidence: 82%
“…However, in addition to its actions on intracellular estrogen receptors, estradiol can also affect a variety of cellular processes through stimulation of surface membrane receptors. Not only have these rapid acting effects of estrogens been shown to play a role in sex behavior, but also in brain and spinal cord regions involved with, but not limited to, learning and memory, motor function, nociception and drug addiction [9][10][11][12][13][14][15]. The majority of these reported membrane-initiated actions of estradiol in the nervous system appear dependent on a subpopulation of ERα and/ or ERβ that are localized to the membrane surface [16][17][18], but see [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The second phase was a non-pain/pain free day, and was defined as the midfollicular phase, prior to ovulation. This phase was chosen because previous studies suggest that pain sensitivity is relatively low [24], and was determined by counting from the first day of menstruation i.e., days 5-9 of an average 28-day cycle.…”
Section: Determination Of Menstrual Cycle Testing Phasesmentioning
confidence: 99%
“…Order of pain stimuli was counterbalanced within gender, with half of the participants receiving the cold followed by the heat stimulus, with this order reversed for the remaining half. Resting blood pressure, menstrual phase and negative mood state were also recorded, as previous research has suggested that these may operate as potential process variables underlying sex and anxiety sensitivity differences in pain (Fillingim and Maixner, 1996;Keogh and Birkby, 1999;Riley et al, 1999).…”
Section: Designmentioning
confidence: 99%